Stem cells, angiogenesis and muscle healing: a potential role in massage therapies? - Best, T. M.; Gharaibeh, B.; Huard, J. (British Journal of Sports Medicine, 2013)
Skeletal muscle injuries are among the most common and frequently disabling injuries sustained by athletes.Repair of injured skeletal muscle is an area that continues to present a challenge for sports medicine clinicians and researchers due, in part, to complete muscle recovery being compromised by development of fibrosis leading to loss of function and susceptibility to re-injury.Injured skeletal muscle goes through a series of coordinated and interrelated phases of healing including degeneration, inflammation, regeneration and fibrosis. Muscle regeneration initiated shortly after injury can be limited by fibrosis which affects the degree of recovery and predisposes the muscle to reinjury. It has been demonstrated in animal studies that antifibrotic agents that inactivate transforming growth factor (TGF)-ß1 have been effective at decreasing scar tissue formation. Several studies have also shown that vascular endothelial growth factor (VEGF) can increase the efficiency of skeletal muscle repair by increasing angiogenesis and, at the same time, reducing the accumulation of fibrosis. We have isolated and thoroughly characterised a population of skeletal muscle-derived stem cells (MDSCs) that enhance repair of damaged skeletal muscle fibres by directly differentiating into myofibres and secreting paracrine factors that promote tissue repair. Indeed, we have found that MDSCs transplanted into skeletal and cardiac muscles have been successful at repair probably because of their ability to secrete VEGF that works in a paracrine fashion. The application of these techniques to the study of sport-related muscle injuries awaits investigation. Other useful strategies to enhance skeletal muscle repair through increased vascularisation may include gene therapy, exercise, neuromuscular electrical stimulation and, potentially, massage therapy. Based on recent studies showing an accelerated recovery of muscle function from intense eccentric exercise through massage-based therapies, we believe that this treatment modality offers a practical and non-invasive form of therapy for skeletal muscle injuries. However, the biological mechanism(s) behind the beneficial effect of massage are still unclear and require further investigation using animal models and potentially randomised, human clinical studies.